FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN SERTA DAMPAKNYA TERHADAP MINAT BELI ULANG SITUS TRAVELOKA (Studi pada konsumen Traveloka di kota Semarang) - Nuraini, Ikka Septya; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2017)
Traveloka is an online site that provides flight reservation services and hotel reservations. However, in 2016 Traveloka for hotel room bookings decreased the number of purchases. This study aims to determine the influence that affect customer satisfaction and its impact on repurchase intention.This study uses 7 variables, which is service quality, brand image, advertisement, price perception, customer satisfaction, trust and interest in repurchase intention. Analysis technique used in this research is Partial Least Square (PLS) 2.0 program.The research results of this study indicate that there are two factors that affect customer satisfaction. First, by providing good service quality. However, the most influential process of repurchase interest is the quality of service that affects the brand image as one of the determinants of success in order to repurchase intention.